Targeting STING: From antiviral immunity to treat osteoporosis - Gao, Zhonghua; Gao, Zhongguo; Zhang, Hao; Hou, Shoubo; Zhou, Yunhua; Liu, Xiangjie (Frontiers in Immunology, 2023)
The cGAS-STING signaling pathway can trigger innate immune responses by detecting dsDNA from outside or within the host. In addition, the cGAS-STING signaling pathway has emerged as a critical mediator of the inflammatory response and a new target for inflammatory diseases. STING activation leads to dimerization and translocation to the endoplasmic reticulum Golgi intermediate compartment or Golgi apparatus catalyzed by TBK1, triggers the production of IRF3 and NF-κB and translocates to the nucleus to induce a subsequent interferon response and pro-inflammatory factor production. Osteoporosis is a degenerative bone metabolic disease accompanied by chronic sterile inflammation. Activating the STING/IFN-β signaling pathway can reduce bone resorption by inhibiting osteoclast differentiation. Conversely, activation of STING/NF-κB leads to the formation of osteoporosis by increasing bone resorption and decreasing bone formation. In addition, activation of STING inhibits the generation of type H vessels with the capacity to osteogenesis, thereby inhibiting bone formation. Here, we outline the mechanism of action of STING and its downstream in osteoporosis and discuss the role of targeting STING in the treatment of osteoporosis, thus providing new ideas for the treatment of osteoporosis.